2017
DOI: 10.3389/fpsyg.2017.00573
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of the Perceived Opportunity to Craft Scale

Abstract: We developed and validated a scale to measure employees’ perceived opportunity to craft (POC) in two separate studies conducted in the Netherlands (total N = 2329). POC is defined as employees’ perception of their opportunity to craft their job. In Study 1, the perceived opportunity to craft scale (POCS) was developed and tested for its factor structure and reliability in an explorative way. Study 2 consisted of confirmatory analyses of the factor structure and reliability of the scale as well as examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 37 publications
3
49
0
1
Order By: Relevance
“…Managers who give their employees autonomy in their job and (positive) feedback on their previous job crafting behavior, may positively affect the employees perceived opportunities to craft (see also Wrzesniewski, 2003). This is in line with the findings of a study by Van Wingerden and Niks (2017), which revealed that an employees" perceived opportunities to craft depend on whether or not the employee experience autonomy and opportunities for professional development in his or her work. This all indicates that the assessment of job characteristics by the employee influence his or her perceived opportunities to craft their work.…”
Section: Perceived Opportunities To Craft and Job Craftingsupporting
confidence: 90%
See 1 more Smart Citation
“…Managers who give their employees autonomy in their job and (positive) feedback on their previous job crafting behavior, may positively affect the employees perceived opportunities to craft (see also Wrzesniewski, 2003). This is in line with the findings of a study by Van Wingerden and Niks (2017), which revealed that an employees" perceived opportunities to craft depend on whether or not the employee experience autonomy and opportunities for professional development in his or her work. This all indicates that the assessment of job characteristics by the employee influence his or her perceived opportunities to craft their work.…”
Section: Perceived Opportunities To Craft and Job Craftingsupporting
confidence: 90%
“…Whether or not employees align their job (and work environments) with their own preferences, motives, and passions, may depend on employees" perceived opportunities to craft (Van Wingerden & Niks, 2017;Van Wingerden & Poell, 2017;Wrzesniewski, 2003;Wrzesniewski & Dutton, 2001). Perceived opportunities to craft can be defined as employees" perceptions regarding their opportunities to proactively optimize their own work environment (Van Wingerden & Poell, 2017).…”
Section: Perceived Opportunities To Craft and Job Craftingmentioning
confidence: 99%
“…This has put increasing demands on organizational and employee adaptively and proactivity. These pressures demand proactive employees who take control of their own working life by creating a healthy and motivating environment (7) .In the beginning of the 1st century, the pro-active changes employees make to their jobs as job crafting. The field of occupational health has started to pay increased attention to the concept of job crafting specifically in nursing profession (8) .…”
Section: (4)mentioning
confidence: 99%
“…Job crafting, employees can optimize their work environment and work experience. This may affect both individual and organizational outcomes as wellbeing, performance, and job involvement (7) .Job involvement has been defined as the degree to which a person identifies psychologically with his work, or the importance of work in his total self-image, furthermore, as the degree to which a person's work performance affects his self-esteem. High job involvement helps to increase organizational output by making it a pleasant experience under supportive supervision (13) .…”
Section: (4)mentioning
confidence: 99%
“…Whether or not employees will proactively craft their job, may depend on different factors related to their work environment (van Wingerden & Niks, 2017;van Wingerden & Poell, 2017;Wrzesniewski, 2003;Wrzesniewski & Dutton, 2001). Different studies suggest that employees' actual job crafting behavior in the workplace may depend on job characteristics, such as job demands and job resources (Berg et al, 2010;Ghitulescu, 2007;Lyons, 2008;van Wingerden & Niks, 2017;van Wingerden, Derks, Bakker, & Dorenbosch, 2013;Wrzesniewski, 2003;Wrzesniewski & Dutton, 2001). In addition, recent literature suggests that job demands and job resources may be antecedents of employees' perceived opportunities to craft, which in turn is related to actual job crafting behavior (van Wingerden & Poell, 2017).…”
Section: Introductionmentioning
confidence: 99%